2022
DOI: 10.3389/fnagi.2022.942629
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tau proteins for the diagnosis of mild cognitive impairment and Alzheimer's disease: A systematic review and meta-analysis

Abstract: ObjectiveDetecting plasma tau biomarkers used to be impossible due to their low concentrations in blood samples. Currently, new high-sensitivity assays made it a reality. We performed a systematic review and meta-analysis in order to test the accuracy of plasma tau protein in diagnosing Alzheimer's disease (AD) or mild cognitive impairment (MCI).MethodsWe searched PubMed, Cochrane, Embase and Web of Science databases, and conducted correlation subgroup analysis, sensitivity analysis and publication bias analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Several p-tau biomarkers (p-tau217, p-tau231, and p-tau235) are well-established markers to diagnose AD dementia from non-AD controls. A recent meta-analysis suggested that p-tau217 had better discriminative accuracy for MCI than p-tau181 and p-tau231 ( Chen et al, 2022 ). We recently showed that a new neuropathological biomarker p-tau198 had capability to diagnose MCI cohorts from cognitively normal subjects in brain tissues ( Wu et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Several p-tau biomarkers (p-tau217, p-tau231, and p-tau235) are well-established markers to diagnose AD dementia from non-AD controls. A recent meta-analysis suggested that p-tau217 had better discriminative accuracy for MCI than p-tau181 and p-tau231 ( Chen et al, 2022 ). We recently showed that a new neuropathological biomarker p-tau198 had capability to diagnose MCI cohorts from cognitively normal subjects in brain tissues ( Wu et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…First, it was only recently that Ashton et al pioneered the measurement of P‐tau231 concentrations in plasma (Ashton, Pascoal, et al, 2021). Second, a recent meta‐analysis of eligible literature published before 26 June 2021 provided an integrative account of plasma tau proteins for the diagnosis of MCI and AD (Chen et al, 2022), including only one article on plasma P‐tau231, that is, the groundbreaking research mentioned above (Ashton, Pascoal, et al, 2021). Taken together, it seems that the 5 year time span considered in our study allows for a comprehensive selection of studies with greater retrieval efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The less invasive and cheaper diagnostic techniques are being more commonly required to provide confirmatory evidence of underlying AD pathophysiology. Until relatively recently, our scientific advances in relation to the high‐sensitivity assays opened the opportunity to extend the use of fluid biomarkers to peripheral blood (Teunissen et al, 2022) and a panel of well‐validated blood biomarkers ensued, such as Aβ42/40 ratio (Xu et al, 2022), neurofibrillary light chain (NfL) (Bornhorst et al, 2022) and the newly identified different hyper‐phosphorylated tau (P‐tau) isoforms (Chen et al, 2022). NfL, a robustly increased biomarker in AD (Ashton et al, 2019; Mattsson et al, 2017), is also increased in other neurodegenerative disorders (Ashton, Janelidze, et al, 2021) and upon acute neurological injury (Wihersaari et al, 2021) owing to its characteristic of detecting axonal injury (Khalil et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasensitive blood tests predicting AD pathologies, amyloid‐β, and tau, in the brain have shown potential for both diagnostic and prognostic clinical application. 3 , 4 , 5 , 6 , 7 Among the most promising blood‐based biomarkers are plasma phosphorylated tau 181 (p‐tau181) 8 , 9 and phosphorylated tau 231 (p‐tau231). 10 Other plasma biomarkers that might aid future diagnostics of AD are plasma glial fibrillary acidic protein (GFAP), 11 plasma amyloid‐β 42 to amyloid‐β 40 ratio (Aβ42/Aβ40 ratio), 12 and plasma neurofilament light (NfL).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasensitive blood tests predicting AD pathologies, amyloid‐β, and tau, in the brain have shown potential for both diagnostic and prognostic clinical application 3–7 . Among the most promising blood‐based biomarkers are plasma phosphorylated tau 181 (p‐tau181) 8,9 and phosphorylated tau 231 (p‐tau231) 10 .…”
Section: Introductionmentioning
confidence: 99%